Hemoglobinopathy: Molecular Epidemiological Characteristics and Health Effects on Hakka People in the Meizhou Region, Southern China - Lin, Min; Wen, Ying-Fang; Wu, Jiao-Ren; Wang, Qian; Zheng, Lei; Liu, Gui-Rong; Huang, Yue; Yang, Hui; Lin, Fen; Zhan, Xiao-Fen; Lin, Chun-Ping; Yang, Hui-Tian; et al. (PloS one, 2013)
Hemoglobinopathies are the most common inherited diseases in southern China. However, there have been only a few epidemiological studies of hemoglobinopathies in Guangdong province. Peripheral blood samples were collected from 15299 "healthy" unrelated subjects of dominantly ethnic Hakka in the Meizhou region, on which hemoglobin electrophoresis and routine blood tests were performed. Suspected cases with hemoglobin variants and hereditary persistence of fetal hemoglobin (HPFH) were further characterized by PCR, DNA sequencing, reverse dot blot (RDB) or multiplex ligation-dependent probe amplification (MLPA). In addition, 1743 samples were randomly selected from the 15299 subjects for thalassemia screening, and suspected thalassemia carriers were identified by PCR and RDB. The gene frequency of hemoglobin variants was 0.477% (73/15299). The five main subgroups of the ten hemoglobin variants were Hb E, Hb G-Chinese, Hb Q-Tahiland, Hb New York and Hb J-Bangkok. 277 cases (15.89%, 277/1743) of suspected thalassemia carriers with microcytosis (MCV<82 fl) were found by thalassemia screening, and were tested by a RDB gene chip to reveal a total of 196 mutant chromosomes: including 124 α-thalassemia mutant chromosomes and 72 β-thalassemia mutant chromosomes. These results give a heterozygote frequency of 11.24% for common α and β thalassemia in the Hakka population in the Meizhou region. 3 cases of HPFH/δβ-thalassemia were found, including 2 cases of Vietnamese HPFH (FPFH-7) and a rare Belgian( G)γ((A)γδβ)⁰-thalassemia identified in Chinese. Our results provide a detailed prevalence and molecular characterization of hemoglobinopathies in Hakka people of the Meizhou region. The estimated numbers of pregnancies each year in the Meizhou region, in which the fetus would be at risk for β thalassemia major or intermedia, Bart's hydrops fetalis, and Hb H disease, are 25 (95% CI, 15 to 38), 40 (95% CI, 26 to 57), and 15 (95% CI, 8 to 23), respectively.